Humans as Pedagogical Beings: An Alternative Paradigm for Developing Islamic Education in Indonesia - Burga, Muhammad Alqadri; Damopolii, Muljono (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
Misunderstanding human nature as the central purpose of education has led to inaccuracies in policymaking, pedagogical approaches, and educational practices, resulting in the suboptimal development of human potential. This study aims to analyze human nature as that of pedagogical beings by examining the optimization of fitrah, hearing, sight, and the heart as fundamental human potentials, as well as their implications for the development of Islamic education. This library-based study draws on data from scholarly books and peer-reviewed journal articles, which are analyzed using content analysis. The findings indicate that human potential is integrative in nature, comprising fitrah as the foundational orientation, hearing and sight as epistemic instruments, and the heart as the moral–spiritual core. The integration of these dimensions forms a holistic educational system oriented toward the formation of insān kāmil. These findings imply the necessity of repositioning human nature as the core of educational design through a balanced integration of ‘aqliyyah and qalbiyyah, the integration of knowledge within the curriculum, and the harmonization of Islamic values, cultural contexts, and the demands of global modernity in educational governance.